2021
DOI: 10.3390/agronomy11101895
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Soil Properties and Nutrients by Visible and Infrared Diffuse Reflectance Spectroscopy to Characterize Vineyards

Abstract: Visible, near, and shortwave infrared (VIS-NIR-SWIR) reflectance spectroscopy, a cost-effective and rapid means of characterizing soils, was used to predict soil sample properties for four vineyards (central and north-western Spain). Sieved and air-dried samples were measured using a portable spectroradiometer (350–2500 nm) and compared for pistol grip (PG) versus contact probe (CP) setups. Raw data processed using standard normal variate (SVN) and detrending transformation (DT) were grouped into four subsets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
5
14
1
Order By: Relevance
“…Such differences in the model performances were found in previous studies. Similar to our results, it was reported that calibration, validation, and prediction processes can be complicated and dependent on soil types and its physiochemical properties, the soil management history, chemical characteristics, and the analytical method, along with the sample size and distribution, as well as the prediction approaches [4,7,13,14,[27][28][29]54,61]. Based on 2250 soil samples that were collected in a 5-year period from four soil groups varying in clay mineralogy (Alfisols, Inceptisols, Entisols, and Vertisols) and a series of robust regression analyses, Golia and Diakoloukas [61] concluded that several factors (pH, electric conductivity, SOC, soil texture, exchangeable cations, and metal oxides along with coexisting metals) affect the total concentrations of Fe and Cd in soils.…”
Section: Accuracy Analysis Of the Plsr Modelssupporting
confidence: 89%
See 3 more Smart Citations
“…Such differences in the model performances were found in previous studies. Similar to our results, it was reported that calibration, validation, and prediction processes can be complicated and dependent on soil types and its physiochemical properties, the soil management history, chemical characteristics, and the analytical method, along with the sample size and distribution, as well as the prediction approaches [4,7,13,14,[27][28][29]54,61]. Based on 2250 soil samples that were collected in a 5-year period from four soil groups varying in clay mineralogy (Alfisols, Inceptisols, Entisols, and Vertisols) and a series of robust regression analyses, Golia and Diakoloukas [61] concluded that several factors (pH, electric conductivity, SOC, soil texture, exchangeable cations, and metal oxides along with coexisting metals) affect the total concentrations of Fe and Cd in soils.…”
Section: Accuracy Analysis Of the Plsr Modelssupporting
confidence: 89%
“…In accordance with recent studies, K is one of the complex elements to estimate with VIS-NIR spectra regardless of the extraction procedure. For instance, good model was obtained by Rodríguez-Pérez et al [7], whereas Bilgili et al [13] found a poor model (R 2 = 0.25-0.32) for the K content. Chang et al [27] obtained a more accurate model (R 2 = 0.64) for K extracted in M3 compared to K extracted in NH4OAc (R 2 = 0.55).…”
Section: Accuracy Analysis Of the Plsr Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were also observed in wavelength range 1900–2500 nm with R 2 c and R 2 p of 0.460 and 0.336 for hulled and 0.382 and 0.274 for naked oats, respectively, whereas in the spectral range from 700 to 1300 nm, the R 2 c and R 2 p for naked oats were 0.677 and 0.620, and the highest values for R 2 c (0.789) and R 2 p (0.735) and the minimum values for RMSEC (0.177) and RMSEP (0.199) were observed for the hulled oat samples. Previously, it was mentioned that the calibration models with R 2 c between 0.66 and 0.81 present satisfactory predictions whereas prediction of chemical properties with R 2 c < 0.5 are reported as being unreliable [ 32 , 33 , 34 ]. A study by Seefeldt et al also reported the best correlation of β -glucan of barley with the wavelengths in these regions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%